Analysis of the shots according to set playing (6-6) position in waterpolo at European B Waterpolo Championships in Lugano 2009 - Ozkol, Z.; Turunc, S.; Dopsaj, M. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: The aim of the present study was to analysis the shoots according to set playing (6-6) position in waterpolo matches at 2009 European Waterpolo B Championships in Lugano. METHODS: Therefore totaly 14 waterpolo matches including 10 teams shoots analyzed with Waterpolo Match Analysis Program (WP_Pro_Analiz, Izmir-Turkiye, 2009), PC using statistic software program SPSS for Win, release 11.0.0 - Standart Version (Copyright© SPSS Inc., 1989- 2001) and excel program. The following parameters analyzed for the shoots; the ending point of the shoots in the goal, fake number of achieved shoots, preliminary position of the shoots and the shoots distance achieved from the goal. RESULTS: From the important findings of the analysis, the % 34.1 (157 shoot) of the total 460 shoot ending at the left down side in the goal, the % 30.4 (140 shoot) of the total 460 shoot achieved from the position 3 (P3) but only % 19.3 (27 shoot) scored of the total 140 shoot from this position (P3), the % 41.5 (191 shoot) and % 33.9 (156 shoot) of the total 460 shoot achieved with no fake and one fake respectively, the % 50.7 (233 shoot) and % 21.5 (99 shoot) of the total 460 shoot achieved from set (6-6) position shoot and fast break shoot respectively, the % 10 (46 shoot) of the total 460 shoot achieved from the center position, the % 9.6 (44 shoot) and % 8.3 (38 shoot) of the total 460 shoot achieved with cross-pass shoot and faul shoot respectively and the last important finding the % 59.1 (271 shoot) of the total 460 shoot achieved from 5-7m away from the goal. DISCUSSION: The present study provided effective information on the achieved shoots in the waterpolo games and also the findings is usefull to the coaches for different game strategies, usefull for the goalie and the field players for whom specialization for the shoot.